2010
DOI: 10.4103/0974-1208.63115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin C and ethanolic extract of Sesamum indicum in promoting fertility in male Wistar rats

Abstract: AIMS:This study investigates the efficacy of ethanolic extract of Sesamum indicum (EES), vitamin C (VC), and EES + VC in promoting fertility and finding a possible link between their profertility effects and their antioxidant activities.MATERIALS AND METHODS:Forty adult male Wistar rats [Body weight (BW) 186.56 ± 0.465 g] were randomly analyzed into four groups of ten rats each: Control, EESG (EES only), VCG (vitamin C only), and EES + VCG (EES in conjunction with vitamin C). Control was given 5 ml/kg BW/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Vitamin C is a strong antioxidant that facilitates the formation of testosterone, and was found in a considerable concentration in tiger nut in this study. It has been reported that vitamin C increases testosterone content in rat testis in vitro [ 35 ], and oral administration of vitamin C for 10 weeks significantly increased serum testosterone levels in male rats [ 36 ]. Moreover, vitamin C supplementation attenuated testosterone deficiency and some male reproductive deficits induced in hyperglycemic rats [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is a strong antioxidant that facilitates the formation of testosterone, and was found in a considerable concentration in tiger nut in this study. It has been reported that vitamin C increases testosterone content in rat testis in vitro [ 35 ], and oral administration of vitamin C for 10 weeks significantly increased serum testosterone levels in male rats [ 36 ]. Moreover, vitamin C supplementation attenuated testosterone deficiency and some male reproductive deficits induced in hyperglycemic rats [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male infertility is caused by a wide range of etiologies. Numerous factors are defined with unequivocal and harmful effect on male reproduction function, i.e., (i) modern (sedentary) life style problems like obesity, smoking, caffeine, alcohol, and drug abuse, (ii) nutritional deficiencies including vitamin and mineral deficiencies [ 9 ] and oxidative stress [ 10 ], (iii) genetic causes related to male infertility like the cystic fibrosis transmembrane conductance regulator (CFTR) gene mutations leading to congenital absence of the vas deferens, Y-chromosome microdeletions in the azoospermia factor locus leading to spermatogenic impairment, and karyotype abnormalities, oncological diseases, (iv) hormonal issues encompass: hyperprolactinemia, hypothyroidism, congenial adrenal hyperplasia, hypogonadotropic hypogonadism, and panhypopituitarism, (v) physical problems likewise varicocele, damaged sperm ducts, torsion, Klinefelter's syndrome, retrograde ejaculation, psychological issues comprised of erectile dysfunction, premature ejaculation, and ejaculatory incompetence [ 11 , 12 ]; hence, different approaches are required to resolve all these multifaceted dilemmas [ 13 ]. Oligospermia may be considered as a pathologic effect of the above-mentioned causes and consequently oligospermia represents a cause of reduced male fertility [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sesamin, a lignan isolated from the seeds of S. indicum plants and sesame oil, has several important biological properties, including antioxidant and anti-inflammatory activities ( Zhou et al, 2015 ). Preclinical investigations have demonstrated that sesame and sesame oil exhibit potent effects on male factor infertility, and the clinical potential of these compounds has also been highlighted by other studies, further substantiating their role as fertility agents ( Ashamu et al, 2010 ; Abbasi et al, 2013 ; Khani et al, 2013 ).…”
Section: Introductionmentioning
confidence: 82%
“…For instance, sesame can effectively improve male semen parameters because of its antioxidant properties, which is a safe and effective method for the treatment of male spermatogenic dysfunction ( Khani et al, 2013 ). The vitamin C and ethanol extract of sesame can improve the fertility of rats through antioxidant effect ( Ashamu et al, 2010 ). Other studies have shown that sesame oil can improve germ cells and support cells of diabetic rats to varying degrees and can dose-dependently increase the plasma testosterone concentration of diabetic rats ( Abbasi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%